If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -35) = 5x Reorder the terms: 7(-35 + x) = 5x (-35 * 7 + x * 7) = 5x (-245 + 7x) = 5x Solving -245 + 7x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -245 + 7x + -5x = 5x + -5x Combine like terms: 7x + -5x = 2x -245 + 2x = 5x + -5x Combine like terms: 5x + -5x = 0 -245 + 2x = 0 Add '245' to each side of the equation. -245 + 245 + 2x = 0 + 245 Combine like terms: -245 + 245 = 0 0 + 2x = 0 + 245 2x = 0 + 245 Combine like terms: 0 + 245 = 245 2x = 245 Divide each side by '2'. x = 122.5 Simplifying x = 122.5
| 15b^2+6b=4b+10b^2+14 | | 4x-2(x-2)=-4+5x-10 | | 24-6x=10+8x | | x-(-14)=-2 | | -0.004*4.2= | | -6(7x-5)=72 | | (4b^9)= | | x+log(x)=0 | | 8x+17-7x=-3-12 | | 3.6+(-0.6)= | | x+(-3)=-3 | | 3.6+(-6.5)= | | 55=x^2*3.14 | | 53y=13(4y+30) | | 28+24x=42+17m | | 45=x^2*3.14 | | 5k+3-3k=6k | | -6(3+7x)=-438 | | xy+y=x | | 7(35x)=5x | | 35=x^2*3.14 | | 3(3x-9)=9 | | 1.63-0.9= | | 9x+1=60+10x | | 19x+3=18x-16 | | 30=x^2*3.14 | | (x-p)=4 | | 6a+5b=12c | | 3(t+6)-16=-7 | | 39.30=6s+3.48 | | z+3.1=12.1 | | 5+3(1+2(2x-3))+1=2x-3 |